The structural, functional and electrophysiological assessment of paraspinal musculature of patients with ankylosing spondylitis and non-radiographic axial spondyloarthropathy - ÖZTÜRK, EKİM CAN; YAĞCI, İLKER (SPRINGER HEIDELBERG, 2021)
Paravertebral muscles are affected in spondyloarthritis. Decreased mobility of spine may lead to atrophy and fatty degeneration of these muscles. The objective of this study was to compare the sonographic, electrophysiological and magnetic resonance imaging (MRI) features of paraspinal muscles between patients with ankylosing spondylitis (AS) and non-radiographic axial spondyloarthritis (nr-axSpA). The patients who were diagnosed as AS with modified New York criteria and those as nr-axSpA with ASAS 2009 criteria were enrolled. Clinical evaluation, electrophysiological examination including nerve conduction studies and needle electromyography (EMG) for lower extremities and paraspinal mapping (PSM) were performed by the first examiner. The second examiner measured lumbar multifidus areas, graded the fatty degeneration of the muscle at different levels in T2 weighted axial MRI and also performed the ultrasonographic evaluation. A total of 19 patients with AS and 14 patients with nr-axSpA were evaluated. MRI of 2 patients with AS could not be obtained. Right lumbar multifidus area/vertebra area (MV ratio) was smaller in AS patients at L3 level (p 0,029); there were no significant differences in other levels. Fatty degeneration was also higher in AS patients in left multifidus at L5-S1 disc level (p 0,015). PSM scores that demonstrate the extent of denervation in paraspinal muscles were significantly higher in AS patients than in nr-axSpA patients (p < 0,001). Patients with AS have more fatty degeneration and denervation in paraspinal muscles. These processes may also contribute the severity of pain and disability. The relationship between paraspinal muscle denervation and progression of fatty degeneration should further be revealed.
Keywords: Paraspinal mapping; Multifidus; Electromyography; Ankylosing spondylitis; Non-radiographic axial spondyloarthritis; Ultrasonography